Investigation of stress concentration factors in countersunk holes of biaxially loaded isotropic plates - Jabri, Abdullah A.; Gharaibeh, Mohammad A. (Zielona Góra: Uniwersytet Zielonogórski)
This study employs finite element analysis (FEA) and response surface methodology (RSM) to analyze the stress concentration factor (SCF) in a biaxially loaded isotropic plate with a central countersunk hole. A finite element model is built using ANSY and employed to generate stress concentration factor values. The finite element model was optimized in terms of mesh density and properties based on data from past literature.
Keywords: countersunk hole; finite element analysis; stress concentration factor; ANSYS; biaxial loading